Learning Innovation in Islamic Boarding Schools in East Java: Technology’s Role in Enhancing Teaching Effectiveness - Abidin, Zainal; Qusairi, Ahmad; Hanifansyah, Nur; Mubarak, Fadhel (TARBIYA: Journal of Education in Muslim Society, 2025)
Abstract Despite the increasing adoption of technology in education, Islamic boarding schools (pesantren) remain underexplored in terms of sustainable digital integration aligned with Islamic values. This study offers a comprehensive exploration of technology-based learning innovations within pesantren, examining how these innovations enhance pedagogical effectiveness while integrating principles of Islamic education management. Conducted as an in-depth qualitative case study across three pesantren in East Java, data were gathered through interviews, classroom observations, and documentation analysis. The study identified three core innovations: the use of digital learning media, the implementation of e-learning platforms, and the integration of mobile applications. These approaches have positively impacted student motivation, learning flexibility, and teacher-student engagement. However, challenges such as limited infrastructure and inadequate digital literacy among educators persist. Findings underscore the need for systematic teacher training, infrastructure investment, and culturally relevant digital leadership to ensure sustainable transformation. The study contributes to both academic discourse and practical policy development by offering context-specific recommendations for integrating technology in pesantren education without compromising core Islamic values. Abstrak Meskipun adopsi teknologi dalam pendidikan semakin meningkat, pondok pesantren masih relatif kurang dieksplorasi terkait integrasi digital yang berkelanjutan dan selaras dengan nilai-nilai Islam. Studi ini menawarkan eksplorasi komprehensif tentang inovasi pembelajaran berbasis teknologi di lingkungan pesantren, dengan menelaah bagaimana inovasi-inovasi tersebut meningkatkan efektivitas pedagogis sekaligus mengintegrasikan prinsip-prinsip manajemen pendidikan Islam. Penelitian ini dilakukan sebagai studi kasus kualitatif mendalam pada tiga pesantren di Jawa Timur, dengan data diperoleh melalui wawancara, observasi kelas, dan analisis dokumentasi. Studi ini mengidentifikasi tiga inovasi utama: penggunaan media pembelajaran digital, implementasi platform e-learning, dan integrasi aplikasi berbasis mobile. Pendekatan-pendekatan ini berdampak positif terhadap motivasi peserta didik, fleksibilitas belajar, serta interaksi guru dan siswa. Namun demikian, tantangan seperti keterbatasan infrastruktur dan literasi digital pendidik yang belum memadai masih menjadi hambatan. Temuan penelitian ini menekankan pentingnya pelatihan guru yang sistematis, investasi infrastruktur, dan kepemimpinan digital yang relevan secara kultural untuk memastikan transformasi yang berkelanjutan. Studi ini memberikan kontribusi pada wacana akademik maupun pengembangan kebijakan praktis melalui rekomendasi kontekstual terkait integrasi teknologi dalam pendidikan pesantren tanpa mengorbankan nilai-nilai Islam yang esensial.